Harmony in Confucianism and how the communist party is using it in contemporary China - Xie, Xiawen (My University, 2025)
Although Confucianism has a long history of influence in China, it was criticized at the beginning of the PRC and then reintroduced since China's open up policy. The purpose of this thesis is to discuss what is harmony in Confucianism and how the Chinese Communist party is using this tradition to solve social problems and meet the challenges in contemporary time. Empirical research and qualitative methods have been used in the paper. First, method is conceptual approaching the classics to find what is the original meaning of harmony in Confucianism. Then focusing on its use in the PRC: in the Mao's era, class struggle was the key line, and Confucianism was regarded with less value. After Mao's death, and since opening to the world since the late 1970s, China has met lots of challenges inside and outside. Under these circumstances, class struggle has been abandoned. Chinese leaders have reflected on and re-expressed harmony in Confucianism, in order to find the solutions to the problems and challenges inside and outside of China in contemporary age. Finally, as the conclusion of this thesis it is argued that while harmony is not a new concept, the CCP is re-interpreting this tradition to suit the situation in contemporary of China. Unlike classical Confucianism defining harmony based on ritual or cultural context, the CCP has reflected this concept on national perspective, between human being and nature, and on international atmosphere. During Hu Jintao as Party General Secretary, the CCP put forward the concept of socialist harmonious society in handling the relationship between reform, development, and social stability. When Xi Jinping succeed the leadership, he first proposed that “Lucid waters and lush mountains are invaluable assets”. The purpose of this concept was to value the harmonious relationship between man and nature in solving environmental problems. Xi further promoted building a community with a shared future of mankind to meet the challenges in international dimensions, as China following a peaceful development for good cooperation and mutual benefits with people of all countries.
Keywords: Confucianism, harmony, China, tradition, the Communist Party